Tinjauan Yuridis Penyelesaian Perselisihan Hak (Upah) Antara Pekerja Dan Pengusaha Di Pengadilan Hubungan Industrial Pada Pengadilan Negeri Ygyakarta Kelas IA - Al Syifa Indriyani; Mustika Prabaningrum Kusumawati (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research describes the practice of resolving workers/laborers' rights (wages) disputes with employers in the Industrial Relations Court at the Class IA Yogyakarta District Court. The aim of this research is to answer the following problems: First, to find out how rights (wage) disputes between workers and employers are resolved in the Industrial Relations Court at the Class IA Yogyakarta District Court. Second, the authority of the Industrial Relations Court at the Class IA Yogyakarta District Court to provide legal certainty regarding rights (wage) disputes between workers and employers in the City of Yogyakarta. The research method used is: normative-empirical. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. This research is descriptive analytical and qualitative data analysis. The results of the research show: First, there are many worker/laborer rights disputes due to non-payment of wages, in the resolution mechanism the Industrial Relations Court at the Class IA Yogyakarta District Court experiences problems in executing decisions. Second, the Industrial Relations Court is considered to have succeeded in exercising its authority as stipulated, in order to realize legal certainty for the parties.